A escolarização da população pobre na Parahyba do Norte: instruir para civilizar, 1855 – 1889 - Santos, Lays Regina Batista de Macena Martins dos (2016)
This dissertation has as objective to analyze the schooling of the poor population in the Province of North Parahyba as part of the process of institutionalization of primary public instruction between the years of 1855, the first words found in the reports of the presidents of the Province about the existence of poor students in the primary public classes. And 1889, because to have marked the politics and the society of the time with the change of political regime. For the construction of the narrative, we elected as the main sources of the reports of the presidents of the Province, the reports of the General Director of the instruction, the laws and regulations of public instruction, newspapers circulated in the Province during the studied period, memoir writers of books, official information published in the 1872 demographic sense and the many documents about public instruction, among them requests, crafts and undersigned intended for Provincial Assembly, as well as bibliography produced about the history of education and of the history of education in Paraíba. The choice of sources has contemplated the information contained on the instruction and society in the North Parahyba in the 19th century. From the theoretical framework of social history, we seek to seize the documents information about the experiences "of subalterns from its own specificities constituents". I.e., analyze the social interactions of these subjects until then submissive to society from the capital that composed the economic elites of the time. The methodological approach considered the organization of instruction in the Province from the operation of the classes of first letters highlighting the perceived conflicts in the schooling process, as well as striving to a critical reading not directly directly assimilate the official speeches and don’t reproduce them as absolute truths. In the course of the research we realized that the ideal of instruction thought at the time was linked to the need of the nation in a project of civilization based on the discourse of men of the time who believed that the access to instruction would lead to the liberation of the people of ignorance, reconfiguring a moral guided in the development as a form of social progress. What characterizes, this way, a civilized society. Thus, from the analyzes carried out on the “black people” and economic profile of Paraíba population and conditions which was the primary public instruction in the Province and from, in particular, four cases of primary public classes that presented themselves as lessons aimed at this population, we conclude that the poor population had access to the first letters in public school of Paraíba eighteenth century.